Evaluation of ELISA and IHA for the detection of agglutinins in goats vaccinated with an experimental killed Mycoplasma mycoides subsp capri saponin vaccine - RANA, RAJNEESH; SRIVASTAVNA, N C; SINGH, V P; SRIVASTAVA, S K (The Indian Journal of Animal Sciences, 2014)
An indirect ELISA was used for the first time to detect Mycoplasma capri antibodies in goats and was compared withindirect haemagglutinatioll test. Goats (36) under 1 year of age and of either sex (negative for M.capri antibodies) were used in 3 groups of 17,17 and 2. Two different freeze-dried M.capri saponin vaccines i.e. vaccine A (protein concentration 1.0 mg/dose) and vaccine B (protein concentration 1.5 mg dose) were prepared and inoculated in 2 different group of goats (17 animals in each group). Indirect haemagglutination test could detect early antibodies whereas; ELISA could detect both early and late antibodies. Enzyme linked immunosorbent assay was adjudged to be comparatively superior for the detection of M.capri agglutinins.